Case method for digital natives teaching and research - Dey, Ajoy kumar [ed.]; Mishra, Shreya [sub-ed.] (New Delhi Blooomsbury India, 2021)
As the year 2021 marks hundred years of Case Method, this book is dedicated to its various dimensions in teaching and research. The Case Method has been used extensively around the world to inculcate, analytical skills, decision making and critical thinking among management students. Similarly, research using this methodology has provided the academia with various theories and models that have been widely used in research and practice. Given its immense contribution in academia and research, 36 case experts and enthusiasts from 11 countries, have contributed to this book through 24 articles distributed in seven sections. These articles highlight how the said method has evolved and how it will be critical in developing the 21st Century Skills in teaching and research.
100 years of case method
Keywords: Case methods